2000
DOI: 10.1097/00006231-200012000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative gated SPECT myocardial perfusion imaging with 201Tl: an assessment of the limitations

Abstract: Gated SPECT (GSPECT) perfusion imaging has been increasing in popularity both with 99Tc(m) agents and 201Tl. However, both higher activities than administered in the UK and multi-headed cameras are often used. The aim of this study was to assess GSPECT imaging using lower activities of 201Tl with a single-headed camera. Seventy patients underwent stress and redistribution GSPECT imaging after a mean injected activity of 62 +/- 7 MBq 201Tl. These patients also underwent radionuclide ventriculography (RNVG) imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 6 publications
3
6
1
Order By: Relevance
“…The EF correlation coefficients between LVG and GPS as well as between GPS and RVG were in the range of previously reported literature(LVG-GPS EF, R = 0.62-0.97; GPS-RVG EF, R = 0.53-0.94) [3,7,8,[23][24][25][26][27][28][29]. No reported data exists regarding the comparison of LVG and 4DM EF data.…”
Section: Ef and Volume Comparisonsupporting
confidence: 68%
“…The EF correlation coefficients between LVG and GPS as well as between GPS and RVG were in the range of previously reported literature(LVG-GPS EF, R = 0.62-0.97; GPS-RVG EF, R = 0.53-0.94) [3,7,8,[23][24][25][26][27][28][29]. No reported data exists regarding the comparison of LVG and 4DM EF data.…”
Section: Ef and Volume Comparisonsupporting
confidence: 68%
“…17 Others concluded that LVEF assessment by Tl-201 gated SPECT is as reliable as gated Tc-99 m-sestamibi. 18 Although many studies are characterized by poor or fair E58 Clin.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, however, in clinical trials adenosine proved at least equivalent to inotropic stressors. [2][3][4] The study by Jagathesan et al 5 adds to the mechanistic explanation of this observation. In 36 patients with single-vessel CAD and 18 healthy volunteers the response to either dobutamine or adenosine stress was assessed with positron emission tomography and 15 Olabeled water.…”
Section: See Related Article P 324mentioning
confidence: 90%